Esferas públicas como uma categoria fundante da gestão social - Garcia, André Spuri (2016)
Once the diagnosis of the importance of the public sphere category to the field of social management and its 'ownership' are still limited, we present in this paper, a reconstruction of the concept through extensive literature accompanying discussions on it the habermasian scope. Therefore, we seek to understand the changes, criticism and reformulations of the public sphere category in the works of Habermas (1962, 1981, 1992). In this process, we reveal that the public sphere has changed and that the most current concepts cover various topics and a plurality of public and conflictive dimensions - through various criticisms and modifications have been expanded analytical potential, descriptive and critical of the public sphere for a variety of companies in different historical times. Before that, a comprehensive literature review was developed on the field of social management with emphasis on the various concepts, origins, its importance, the various approaches and the debates and criticisms about the concepts. In the relationship between social management and public sphere, we highlight limitations when it comes to there are few discussions with critics of Habermas' concept and on subaltern public spheres, counter-hegemonic and not problematize its plurality; there is also focus only on work Structural Transformation of the Public Sphere, in which the author made his first and most contested systematize; the studies do not discuss even the reformulation of the public sphere concept and there is little consideration about the socio-cultural, economic and brazilian politics.. Finally, we reconstruct the public sphere as an empirical-descriptive and normative category of social management. We argue that if we consider the public sphere (public spheres) as a locus of social management (normative and empirical), it is important to address the specifics of the brazilian context to strengthen their own social management. In this sense, the reconstructions undertaken here do not treat Brazil as 'delayed' democratically and has not yet reached modernity and therefore cannot appropriate the ideal habermasian. On the contrary, the search capabilities of Habermas to 'think Brazil' and forms of management. Thus, we seek to argue that the reconstruction shows the descriptive, normative and critical potential of the public sphere idea, especially if the expanded and explored its development from Habermas, its reviewers and critics - opening avenues for the theoretical, practical and methodological development of social management, from which can tighten the management practices and their potential emancipatory and pathological-enforcement (in its various configurations).